Adolescent identity development in parental divorce experienced family - Vaičiulienė, Aldona (Psichologija, 1999)
This research examines differences in identity development among 16-17 years old adolescents who came from divorced and intact families. Using a sample of 307 secondary school students (238 from intact families and 69 from divorced families) were assessed an identity level. The findings indicate some not very strong tendencies. Adolescents from divorced families are less foreclosed then adolescents from intact families, therefore they are less dependent on family traditions, values, believes. Adolescents from divorced families fall into identity crisis some earlier and stay in it some longer then adolescents from intact families.